The Effect Of A Counseling Program Based On Remy's Theory To Reduce Self-Alienation Among University Students In The Internal Departments (Journal of the College of Basic Education, 2024)
The phenomenon of alienation is one of the most cruel social phenomena in society and the lives of individuals, and it is a complex phenomenon that is not limited to the social, psychological or cultural dimension, but is the result of the interaction of these aspects in the context of the absence of justice and the power of everything that is material and inhuman. The current research aimed to identify the impact of a counseling program based on Remy's theory to reduce self-alienation among university students in the internal departments. To achieve the objective of the research and its hypotheses and verify the hypotheses, the researcher used the experimental design with experimental and control groups with pre- and post-tests, where the research sample consisted of (60) students after the psychometric characteristics of the approved program were verified (with honesty and stability). To complement the current research, the researcher came up with a series of recommendations and suggestions